The Effect of Business Model Innovation and Entrepreneurship Orientation on MSMESs Performance Through Business Agility Moderated Financial Literature - Dinda Riri Saraswati; Pristiyono Pristiyono; Aziddin Harahap (Quantitative Economics and Management Studies, 2022)
This study aims to examine the effect ofbusiness model innovation and entrepreneurial orientation towards MSMES performance through business agility moderated by financial literacy.The approach used in this research is quantitative. In this study, researchers used incidental sampling which obtained 100 respondents. The analysis used in this study is a structural approach to the Equation Model (SEM) assisted by the smart PLS. application (Ghozali & Latan, 2015). Based on the research findings, it can be concluded that entrepreneurial orientation, business model innovation, and business agility affect the performance of MSMESs, business model innovation and entrepreneurial orientation are known to affect business agility. Meanwhile, financial literacy has not been able to moderate the relationship between business agility and MSMES performance. Business agility is able to mediate the relationship between business model innovation and Entrepreneurial Orientation on the performance of MSMESs.